2014
DOI: 10.1371/journal.pone.0097337
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Intron 1 and Intron 22 Inversion Negative Haemophilia A Patients from Western India

Abstract: Despite increased awareness and diagnostic facilities, 70–80% of the haemophilia A (HA) patients still remain undiagnosed in India. Very little data is available on prevalent mutations in HA from this country. We report fifty mutations in seventy one Indian HA patients, of which twenty were novel. Ten novel missense mutations [p.Leu11Pro (p.Leu-8Pro), p.Tyr155Ser (p.Tyr136Ser), p.Ile405Thr (p.Ile386Thr), p.Gly582Val (p.Gly563Val) p.Thr696Ile (p.Thr677Ile), p.Tyr737Cys (p.Tyr718Cys), p.Pro1999Arg (p.Pro1980Arg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
1
12
0
3
Order By: Relevance
“…The results with regard to the large deletion frequency and the single mutations observed in our study were comparable to HGMD; furthermore we found four novel mutations from the 18 mutations. This present a frequency about 22.22% which is comparable to early publication [2]. The clinical data of the samples with single mutation in Table 2B showed that the patient present <1% of factor VIII (severe hemophilia) with episodic bleeding and the patients were on one or more than one treatment regimens.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results with regard to the large deletion frequency and the single mutations observed in our study were comparable to HGMD; furthermore we found four novel mutations from the 18 mutations. This present a frequency about 22.22% which is comparable to early publication [2]. The clinical data of the samples with single mutation in Table 2B showed that the patient present <1% of factor VIII (severe hemophilia) with episodic bleeding and the patients were on one or more than one treatment regimens.…”
Section: Discussionsupporting
confidence: 75%
“…The region for F8 gene is characterized with a high GC content and within the 9.1 kb coding region there are about 70 CpG dinucleotides. This resulted into hyper-mutation and approximately 30% of variants are usually novel [2]. A total of 2320 mutations so far have been reported in F8 gene in the Human Gene Mutation Database (HGMD) [3].…”
Section: Introductionmentioning
confidence: 99%
“…B). In Indian and Iranian patients, representing 35% and 13% of our cases, the mutation distribution was similar to those in previous reports from those countries .…”
Section: Resultsmentioning
confidence: 99%
“…The mutation in intron has not been reported previously, and whether the mutation in the intron influences the correct transcription and translation of F8 gene, and protein folding, remains unclear. However, the mutation c.2087C>T (exon 13), resulting in the Thr 696 Ile amino acid change, has been reported in a Indian patient with moderate haemophilia (FVIII:C 3%) who had two mutations: c.2087C>T (exon13) p.Thr696Ile and c.6951C>G (exon26) p.Arg2228Gln [8]. Similarly, a patient with mild haemophilia (FVIII:C 6%) with the mutation c.2087C>A (exon13) p.Thr677Asn has been reported in the UK [9].…”
Section: Discussionmentioning
confidence: 99%